An analysis of operationalization and acceptability of business to business transaction: a mixed method approach - Owolabi Yusuf, Muhammad-Bashir; Mydin Meera, Ahamed Kameel; Mat Ghani, Gairuzazmi; Abdul Manap, Turkhan Ali; Larbani, Moussa (Science Publications, 2012)

(untitled)
Business to business barter exchange is a form of transaction that is gaining popularity during the economic downtown despite the fact that money exchange supersede the traditional barter exchange due to a number of inherent problems it has. This study explores the operation and user’s acceptance of business to business barter exchange in Malaysia that has made barter exchange feasible in the present day sophisticated financial system. Mixed method data analysis was employed to analyze the qualitative and quantitative data collected for the study. The qualitative data was obtained through in-depth interview, observation and document analysis of BBX Malaysia. The quantitative data was obtained from the survey of the BBX members and analysed using PLS technique. The qualitative part explored the operation of BBX from organization through accountability to challenges. The quantitative aspect examined a number of hypotheses to determine the user’s future behavioral intention, premised on a number of previous models. The data was found to fit the model well with all the hypothesized links exhibiting the correct signs and four out of six part coefficients statistically significant. More effort should be made to maximize the factors that determine user’s acceptace of barter exchange in order to achieve its potential.